2021
DOI: 10.1016/j.schres.2020.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of retrieval deficits in autobiographical memory impairment in schizophrenia: A comparison of involuntary and voluntary autobiographical memories

Abstract: Patients with schizophrenia show severe autobiographical memory impairment, thought to reflect retrieval deficits caused by executive dysfunction. However, prior research has focused exclusively on strategic (voluntary) retrieval, and ignored involuntary retrieval resulting from automatic and associative processes, involving minimal cognitive control. We report two studies with patients diagnosed with schizophrenia, (Ns= 40 and 50 respectively) comparing their impairment in involuntary versus voluntary autobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In the aforementioned study by Potheegadoo et al (2014), a specific cueing method improved patients´ ability to recall some, but not all categories of details, therefore suggesting a poor encoding of those details, that remained without benefit by retrieval cues. Moreover, in another recent study the comparison between involuntary and voluntary retrieval of AM revealed a similar impairment of patients in both conditions (Allé et al, 2021). Considering voluntary retrieval as effortful process involving executive functions and involuntary retrieval as a rather automatic process, results argue against solely retrieval problems but rather point to encoding deficits.…”
Section: Overgeneral Am In Schizophreniamentioning
confidence: 77%
“…In the aforementioned study by Potheegadoo et al (2014), a specific cueing method improved patients´ ability to recall some, but not all categories of details, therefore suggesting a poor encoding of those details, that remained without benefit by retrieval cues. Moreover, in another recent study the comparison between involuntary and voluntary retrieval of AM revealed a similar impairment of patients in both conditions (Allé et al, 2021). Considering voluntary retrieval as effortful process involving executive functions and involuntary retrieval as a rather automatic process, results argue against solely retrieval problems but rather point to encoding deficits.…”
Section: Overgeneral Am In Schizophreniamentioning
confidence: 77%
“…Relatively few studies have investigated 'involuntary MTT,' for which past or future events are spontaneously generated when participants are engaged with other tasks. For instance, two recent studies investigated involuntary MTT in patients with schizophrenia (Allé et al, 2020(Allé et al, , 2021. Therefore, future research should compare voluntary and involuntary MTT in psychiatric patients, and conduct cross-diagnosis comparisons of MTT.…”
Section: Mtt Impairments In Psychiatric Patients At the Behavioral Levelmentioning
confidence: 99%
“…As overgeneral memory is a common finding in people with depression (Williams et al, 2007), it would be interesting for future studies to examine whether music can improve this, especially in lieu of the improvements in specificity found in AD. Many other clinical disorders such as schizophrenia (Allé et al, 2021), posttraumatic stress disorder (Ono et al, 2016), and Borderline personality disorder (Van den Broeck et al, 2015) also have AM‐related issues where it could be relevant to investigate MEAMs.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%